Results of screening for metabolic syndrome amongst college participants in Rostov-on-Don, diagnostic criteria - V. I. Kudinov; A. I. Chesnikova; N. V. Zolotareva; M. S. Nichitenko; N. A. Korsun; O. B. Kucherenko; A. A. Tsxaeva; O. B. Mockovets; A. B. Tokareva (Медицинский вестник Юга России, 2010)
Purpose: to confirm the prevalence, identify early markers of metabolic Syndrome (MS) amongst college participants between the ages 16-18 years. Materials and methods: 240 young men and 452 young women were observed, Body Mass Index (BMI), percentage fat composition in the organism of (OMRONBF-306 и BF-400), level of Arterial Blood Pressure (BP) (OMRONM3 Expert). We selected 30 young women with hereditary predisposition to metabolic syndrome. MS and normal body mass index BMI. For the purposes of identification of early markers of metabolic syndrome, further investigations on the blood glucose level, C-Peptide, lipidogram and volume of visceral fats using Computer Tomography (CT) was done. Results: overwheight and obesity was found in 20.3% of participants, they all had an elevated level of fat composition. It was noted that 45.8% of the participants had an elevated level of fat composition but normal body mass index. Among this group with elevated fat composition, 98% was found to have visceral fat content 2-3 times higher than the control figures,72% had disorder of the lipid spectre. Summary: the increasement of volume of BMI, found by CT of abdominal ares is the first objective sign of formation of MS in young people.